(untitled) (American Journal of Islam and Society, 2013)
An Islam of Her Own is a valuable addition to the growing literature on Muslim women’s pietistic subjectivities. Unlike others, however, Sherine Hafez is unsatisfied with the unitary portrayal of the identities of Muslim female activists as a struggle between secular and religious subjectivities. Locating herself and the women she studies at the permeable boundaries of these tropes, her study problematizes the neatly bordered parameters of each and argues, instead, for movement, mobility, and transition between religious and secular spaces. She moves the discussion of religious subjectivities from Saba Mahmood’s influential study of non-liberal subjectivity in the Egyptian women’s mosque movements (p. 11) to “the complexity of negotiation” and the “inconsistent appropriation” of both secular and religious spaces in fashioning desire among female activists (p. 5). The articulation between the secular and religious, Hafez explains, is seamless. Activists move easily in the spaces between “pious self-amelioration and secular political values” (p. 5). They make “normalised distinctions between religion and secularism” that are “liberal in principle and secular in practice,” and yet simultaneously view “Islam as encompassing all aspects of life” (p. 13). These slippages, she argues, confirm that the subjectivities of activist Muslim women in Egypt are “varied, heterogeneous and unstable” (p. 13) and not fully understood when packaged as non-liberal ...